2020
DOI: 10.1155/2020/3067273
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bioinformatics Analysis Identifies ELAVL1 and APP as Candidate Crucial Genes for Crohn’s Disease

Abstract: Immune imbalance and barrier destruction of intestinal mucosa are the central pathogenic factors of Crohn’s disease (CD). In this study, three independent microarray studies of CD were integrated and 9912 differentially expressed genes (DEGs) were analysed by NetworkAnalyst to screen candidate crucial genes. NetworkAnalyst identified ELAV-like RNA binding protein 1 (ELAVL1) as the most crucial upregulated gene and amyloid-β precursor protein (APP) as the most crucial downregulated gene in peripheral blood of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…We applied an integrated bioinformatics analysis to explore key regulators using NetworkAnalyst, a web-based visual analytics platform for comprehensive profiling, meta-analysis and systems-level interpretation of gene expression data (Zhou et al, 2019 ). The utility of NetworkAnalyst for identifying differentially expressed genes (DEGs) and pathways has recently been demonstrated (Santiago and Potashkin, 2015 ; Li et al, 2020 ; Dai et al, 2022 ). For example, network analyses have identified HNF4A and PTBP1 as effective biomarkers for Parkinson's disease (Santiago and Potashkin, 2015 ) and ELAVL1 and APP as crucial candidate genes for Crohn's disease (Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We applied an integrated bioinformatics analysis to explore key regulators using NetworkAnalyst, a web-based visual analytics platform for comprehensive profiling, meta-analysis and systems-level interpretation of gene expression data (Zhou et al, 2019 ). The utility of NetworkAnalyst for identifying differentially expressed genes (DEGs) and pathways has recently been demonstrated (Santiago and Potashkin, 2015 ; Li et al, 2020 ; Dai et al, 2022 ). For example, network analyses have identified HNF4A and PTBP1 as effective biomarkers for Parkinson's disease (Santiago and Potashkin, 2015 ) and ELAVL1 and APP as crucial candidate genes for Crohn's disease (Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 66 It is reported that intestinal fibrosis is alleviated by enhancing the phosphorylation of AMPK in CD, 67 and previous bioinformatics analysis also identified MAPK signaling and PI3K-Akt signaling as crucial signaling pathways for Crohn’s Disease. 52 Another bioinformatics analysis study showed that the levels of autophagy-related proteins in FoxO signaling pathway were higher, but the levels of proteins related to inflammation in the intestinal mucosa were reduced. 68 FoxO4 transcription is temporarily suppressed in TNBS treatment and IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Topological analysis reveals that the APP was the hub gene with the highest number of interactions with the expressed genes in the datasets. In addition, a recent study reported that APP gene is an important DEG for CD disease (Li et al, 2020). These results suggest that some similar genetic factors may be effective in both Alzheimer's disease (AD), and CD as APP is a critical gene in FIGURE 3 | Mapping transcriptome data to UC-specific PPI network for the discovery of subnetworks with KeyPathwayMiner (KPM).…”
Section: Identified Ulcerative Colitis-and Crohn's Disease-specific Subnetsmentioning
confidence: 99%